2014
DOI: 10.1109/jphot.2013.2295467
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence Devices Based on Si Quantum Dots/SiC Multilayers Embedded in PN Junction

Abstract: We deposited a p-i-n structure device with alternative amorphous Si (a-Si) and amorphous SiC (a-SiC) multilayers as an intrinsic layer in a plasma-enhanced chemical vapor deposition (PECVD) system. A KrF pulsed excimer laser-induced crystallization of a-Si/a-SiC stacked structures was used to prepare Si quantum dots (Si QDs)/SiC multilayers. The formation of Si QDs with an average size of 4 nm was confirmed by Raman spectra, whereas the layered structures were revealed by cross-sectional transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…In our previous work, the microstructures, electronic and optical properties of nc‐Si films had been widely investigated in heterogeneous films containing both amorphous and nanocrystalline Si phases . It was found that two different conduction paths controlled by either the transport in the extended states or the hopping conduction via the localized states dominated the carrier‐transport behaviors in the different temperature ranges, which had been revealed in temperature‐dependent conductivity measurements.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous work, the microstructures, electronic and optical properties of nc‐Si films had been widely investigated in heterogeneous films containing both amorphous and nanocrystalline Si phases . It was found that two different conduction paths controlled by either the transport in the extended states or the hopping conduction via the localized states dominated the carrier‐transport behaviors in the different temperature ranges, which had been revealed in temperature‐dependent conductivity measurements.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, nanocrystalline silicon (nc‐Si) films have attracted considerable research interest due to their potential applications in future optoelectronic devices, such as thin‐film transistors (TFT) , thin film solar cells as well as nonvolatile memories . Compared with hydrogenated amorphous silicon (a‐Si:H) films, the nc‐Si films have high electrical conductivity , high charge‐carrier mobility , better stability , and higher absorption in the near‐infrared wavelength range .…”
Section: Introductionmentioning
confidence: 99%
“…8 X. Xu et al used laser crystallization technique to get the p-i-n structures containing nc-Si:SiC films and they observed the improved electroluminescence due to the enhanced radiative recombination probability. 9 Usually, nc-Si:SiC films can be obtained by growing Si-rich SiC films or amorphous Si/SiC multilayers with subsequently thermal annealing at high temperature. [5][6][7][8][9][10][11][12] By controlling the Si/C ratio or the post-annealing conditions, the optical band gap can be tunable which brings convenience to the design of optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…9 Usually, nc-Si:SiC films can be obtained by growing Si-rich SiC films or amorphous Si/SiC multilayers with subsequently thermal annealing at high temperature. [5][6][7][8][9][10][11][12] By controlling the Si/C ratio or the post-annealing conditions, the optical band gap can be tunable which brings convenience to the design of optoelectronic devices. However, the SiC matrix with a large band gap usually has a poor conductive property and in turn impedes the carrier transport process which will deteriorate the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Silica-based semiconductor nanocrystals have attracted much interest in recent years due to their possible applications in many kinds of nanoelectronic and optoelectronic devices such as next generation of solar cells, nonvolatile memories, and single electron transistors [1][2][3][4][5]. Compared with Si, Ge has larger electron and hole mobility, which can be used to fabricate the Ge-based thin film transistor (TFT) and nonvolatile memories with good device performance [6,7].…”
Section: Introductionmentioning
confidence: 99%